INVENTORY OF MEDICINAL PLANT FOR HYPERTENSION PATIENTS IN WATUNOHU VILLAGE, NORTH KOLAKA DISTRICT - rusdam, sulisfa (Makassar Natural Product Journal (MNPJ), 2024)
Indonesia is an archipelagic country which is very broad as a tropical country with very diverse plants in Indonesia. Southeast Sulawesi Province is one of the 34 provinces in Indonesia which has a high level of plant species diversity. Traditional medicine using medicinal plants is still widely used by the people of Watunohu Village, North Kolaka Regency. The purpose of this study was to find out what medicinal plants are used by the people of Watunohu Village to treat hypertension and how to present them. This study used a descriptive method with a qualitative approach. Data collection was carried out by observing and interviewing informants. The sampling technique used was purposive sampling. From the results of the study, it was found that 12 types of medicinal plants were used by the people of Watunohu Village to treat hypertension with the parts used, namely fruits and leaves, by serving them boiled or mashed and then drunk.